2003
DOI: 10.1038/ng1112
|View full text |Cite|
|
Sign up to set email alerts
|

Mice deficient in protein tyrosine phosphatase receptor type Z are resistant to gastric ulcer induction by VacA of Helicobacter pylori

Abstract: The vacuolating cytotoxin VacA produced by Helicobacter pylori causes massive cellular vacuolation in vitro and gastric tissue damage in vivo, leading to gastric ulcers, when administered intragastrically. Here we report that mice deficient in protein tyrosine phosphatase receptor type Z (Ptprz, also called PTP-zeta or RPTP-beta, encoded by Ptprz) do not show mucosal damage by VacA, although VacA is incorporated into the gastric epithelial cells to the same extent as in wild-type mice. Primary cultures of gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
200
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(204 citation statements)
references
References 28 publications
2
200
1
1
Order By: Relevance
“…20 Mouse infections were performed orally with ~10 8 bacteria. Primary gastric epithelial cells were isolated as previously described; 21 the immortalized murine gastric epithelial cell line used in this study was also described previously. 7 Both cell types were grown in DMEM/Ham's F12 medium (1:1; Gibco) supplemented with 10% FCS and infected for 12 hours with H. pylori strains G27 or an isogenic mutant lacking the Cag pathogenicity island (PAI), G27 PAI.…”
Section: Mice Cell Culture Bacterial Infections and Vaccinationmentioning
confidence: 99%
“…20 Mouse infections were performed orally with ~10 8 bacteria. Primary gastric epithelial cells were isolated as previously described; 21 the immortalized murine gastric epithelial cell line used in this study was also described previously. 7 Both cell types were grown in DMEM/Ham's F12 medium (1:1; Gibco) supplemented with 10% FCS and infected for 12 hours with H. pylori strains G27 or an isogenic mutant lacking the Cag pathogenicity island (PAI), G27 PAI.…”
Section: Mice Cell Culture Bacterial Infections and Vaccinationmentioning
confidence: 99%
“…Although VacA is not necessary for gastric ulcer formation, in H. pylori-colonized Mongolian gerbils its presence increases the risk (53). Mice administered VacA orally develop gastric ulcers (54, S28), but mice deficient in the protein tyrosine phosphatase receptor type Z, polypeptide 1 (Ptprz -/-mice) do not (54). Ptprz is one of several puta- The cagA product is injected into the cytoplasm of the host cell, where tyrosine (Y) residues near its COOH-terminus are phosphorylated.…”
Section: A General Model Of Host-microbial Persistencementioning
confidence: 99%
“…Git1 Phosphorylation-BHK-21 cells (2 ϫ 10 5 ), which lack RPTP␤ but contain its substrate Git1, were cultured on Matrigel-coated plates for 24 h in DMEM containing 10% FCS and then transfected with RPTP␤ mutant expression plasmids (9). After cultivation for 24 h, cells were incubated with or without VacA for 1 h at 37°C and then washed twice with ice-cold PBS; this was followed by treatment with N-lysis buffer (20 mM Tris-HCl, pH 7.5, 137 mM NaCl, 1% Nonidet P-40, 0.1% SDS, 0.2% deoxycholic acid, 1 mM sodium orthovanadate, 1 mM NaF, and protease inhibitor) for 30 min on ice.…”
Section: Construction Of Rptp␤-b and Its Deletionmentioning
confidence: 99%
“…Recent molecular and cellular studies of VacA action have shown that it is a major virulence factor that is involved in the pathogenesis of inflammation in H. pyloriinduced gastritis and ulceration (4 -6). In mice, orally administered VacA causes degeneration of the gastric mucosa and acute inflammation followed by gastric ulcer disease (7)(8)(9). In some eukaryotic cells, VacA induces cytoplasmic vacuolation, leading to death.…”
mentioning
confidence: 99%
See 1 more Smart Citation